Predictive Refractive Error Post Congenital and Developmental Cataract Surgery - Eva Imelda; Feti Karfiati; Maya Sari Wahyu; Irawati Irfani; Primawita Oktarima; Sesy Caesarya (Berkala Kedokteran, 2021)
Abstract: Cataract is one of the leading treatable causes of visual impairment in children. Visual rehabilitation is crucial for the development of good visual function after cataract surgery in children. The research aimd to describe post-operative Predictive Refractive Error (PRE) in congenital and developmental cataracts in Cicendo National Eye Hospital from January 2017 to December 2018. This is a retrospective analytic observational study from medical records. We found 107 eyes of 62 children with congenital and developmental cataracts had had cataract surgery and primary implantation of Intraocular Lens (IOL) in Pediatric Ophthalmology and Strabismus Unit, Cicendo National Eye Hospital. The patients were divided into two groups, with axial length (AXL) of ≤ 24 mm and > 24 mm. The paired t-test was used to compare Predictive Error (PE) in SRK/T, SRK II, and Showa SRK formula. Mean age at surgery was 6.7 ± 4.0 years.  Ninety-five eyes had AXL ≤ 24 mm, and 12 eyes had AXL > 24 mm. Prediction Error from patients with AXL ≤ 24 mm was 0.29 D, and from patients with AXL > 24 mm was 2.40 D in SRK/T formula (P < 0.05). There was no significant difference between PE and Absolute Predictive Error (APE) in SRK/T, SRK II, and Showa SRK in patients with AXL > 24 mm (P > 0.05). SRK/T is the most predictable formula in patients with AXL ≤ 24 mm. There is no significant difference in patients with AXL > 24 mm in all formulas. Keywords: congenital and developmental cataract, axial length, Prediction Error, intraocular lens